Fortitude and Fortune: Unveiling the Pillars of Women’s Entrepreneurial Success - Shrestha, Sajeeb Kumar; Mahat, Dipak (Nepal Journal of Multidisciplinary Research, 2024)
Women in Kathmandu Valley are increasingly becoming entrepreneurs, playing a vital role in the region's economic growth. This study aims to understand how factors like training, support from family and government, and having enough money impact women's success in starting and running their businesses. Women entrepreneurs in Kathmandu Valley were interviewed between September and November 2022 to gather their experiences. Special software NVIVO 12 was used to analyze their responses and identify patterns. Findings reveal that training, family support, financial resources, and supportive government policies significantly contribute to women's success in entrepreneurship. While some faced challenges, many expressed positivity about their businesses and the assistance they received. The research underscores the importance of providing training, support, financial resources, and favorable regulations to help more women succeed in business in Kathmandu Valley, benefiting both them and the local economy. This study offers new insights into the factors driving women's entrepreneurial success in Kathmandu Valley, emphasizing the significance of support systems and conducive conditions for business growth.